2014
DOI: 10.1002/dneu.22219
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium and cyclic nucleotide signaling in cerebellar granule cell migration under normal and pathological conditions

Abstract: In the developing brain, immature neurons migrate from their sites of origin to their final destination, where they reside for the rest of their lives. This active movement of immature neurons is essential for the formation of normal neuronal cytoarchitecture and proper differentiation. Deficits in migration result in the abnormal development of the brain, leading to a variety of neurological disorders. A myriad of extracellular guidance molecules and intracellular effector molecules is involved in controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…Furthermore, the authors suggested that the Smoothened-dependent Ca 2+ spike activity is necessary for Shh-induced differentiation of spinal postmitotic neuron. Moreover, the role of second messenger signaling in the regulation of cerebellar granule cell migration has been studied in different mouse models (Komuro et al, 2015), which highlighted the direct evidence of the role of Ca 2+ signaling in granule cell turning and modulation of their migration rate. The revision of these studies, performed by Komuro et al (2015), suggested the role of Ca 2+ as potential therapeutic target for some deficits in granule cell migration since its downstream effectors control the assembly and disassembly of cytoskeletal elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors suggested that the Smoothened-dependent Ca 2+ spike activity is necessary for Shh-induced differentiation of spinal postmitotic neuron. Moreover, the role of second messenger signaling in the regulation of cerebellar granule cell migration has been studied in different mouse models (Komuro et al, 2015), which highlighted the direct evidence of the role of Ca 2+ signaling in granule cell turning and modulation of their migration rate. The revision of these studies, performed by Komuro et al (2015), suggested the role of Ca 2+ as potential therapeutic target for some deficits in granule cell migration since its downstream effectors control the assembly and disassembly of cytoskeletal elements.…”
Section: Resultsmentioning
confidence: 99%
“…These genes belong to the described Smo-dependent non-canonical Shh pathways (Figure 3) that have been reported to modulate cytoskeleton-dependent processes (Jenkins, 2009) and Ca 2+ spikes (Brennan et al, 2012). In particular, a model in which the subcellular compartment (i.e., primary cilium) for Shh signaling allows the spatiotemporal integration of second messengers has been proposed (Belgacem and Borodinsky, 2011), and the role of Ca 2+ signaling in granule cell turning and in modulation of their migration rate has been suggested as potential therapeutic target for some deficits in granule cell migration, since its downstream effectors control the assembly and disassembly of cytoskeletal elements (Komuro et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…We found the highly positive Casq1 cells to be sparse in the molecular layer of adult cerebellum where migrating granules transit (see also Supplementary Figure S5E). It appears that the neuronal migration and the proliferation of granule cells is regulated by Ca 2+ release from ER stores via IP3-and/or ryanodine-sensitive channels (Kumada and Komuro, 2004;Komuro et al, 2015;Horigane et al, 2019). It is plausible that Casq1 plays a role in such a mechanism in fish, especially in shaping either Ca 2+ transients or spikes, as occurs in the skeletal muscle (Tomasi et al, 2012).…”
Section: Differential Cellular Localization Of Casqs: Physiological Imentioning
confidence: 99%
“…Indeed, Ca 21 is a well-known modulator of the cell cycle (Hepler, 1994) and Ca 21 increase can promote the expression of genes involved in the CNS development and can enhance neurogenesis and interneuron differentiation (Ghosh et al, 1994;Rosen et al, 1995;Bito et al, 1997;Ginty, 1997;Brustein et al, 2013). A recent review about granule cell migration in the cerebellum highlights the role of Ca 21 in this process and there are some similarities with the cortex (Komuro et al, 2015). In particular the increase in intracellular Ca 21 enhances the speed of migration and it is when Ca 21 spikes are lost that the migration is complete (Kumada and Komuro, 2004;Komuro and Kumada, 2005).…”
Section: Glycinementioning
confidence: 99%